2023
DOI: 10.5194/egusphere-2023-261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of atmospheric rivers and associated weather systems on precipitation in the Arctic

Abstract: Abstract. In this study, we analyse the contribution of Atmospheric Rivers (ARs), cyclones, and fronts to the total precipitation in the Arctic. We focus on two distinct periods of different weather conditions from two airborne campaigns: ACLOUD (May/June 2017) and AFLUX (March/April 2019). Both campaigns covered the northern North Atlantic sector, the area in the Arctic that is affected by the highest precipitation rates. Using ERA5 reanalysis, we identify pronounced regional anomalies with enhanced precipita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…We find that the atmospheric river components of the WAI contribute about 30% to the total precipitation (27% snowfall, 3% rainfall) at the grid cell nearest to RV Polarstern. A similar magnitude of contribution was calculated during two other campaigns in the Arctic (Lauer et al, 2023). Even larger fractions are discovered further east and south, at the marginal sea ice zone.…”
Section: Precipitation and Snowfallsupporting
confidence: 85%
“…We find that the atmospheric river components of the WAI contribute about 30% to the total precipitation (27% snowfall, 3% rainfall) at the grid cell nearest to RV Polarstern. A similar magnitude of contribution was calculated during two other campaigns in the Arctic (Lauer et al, 2023). Even larger fractions are discovered further east and south, at the marginal sea ice zone.…”
Section: Precipitation and Snowfallsupporting
confidence: 85%
“…We hypothesize that the VR grids will simulate ARs more accurately than the coarser resolution grids through better resolution of finer-scale physical processes and topography, as has been seen in other studies investigating moisture intrusions in the Arctic (Bresson et al, 2022). Accurately modeling precipitation from ARs is important because it has been suggested that during early summer nearly 40% of precipitation in Greenland is due to ARs (Lauer et al, 2023). The model output is compared to ARs detected by ERA5 and MERRA2, two observation-based meteorological reanalysis datasets, as in other studies involving simulated ARs (Bresson et al, 2022;Viceto et al, 2022;Zhou et al, 2022;Mattingly et al, 2023).…”
mentioning
confidence: 77%
“…Strong winds can mix air masses vertically and horizontally, potentially bringing warmer air to the surface from aloft or redistributing air masses in a way that leads to surface warming. Additionally, systematic studies highlight the significant role of ARs in the meridional transport of atmospheric latent heat, affecting climatic parameters in sub-polar regions, with a notable impact in the northern hemisphere due to the absence of constant blocking effects [83], [32]. At the same time, the decrease in mean TN over the Iberian peninsular could be due to the dominating effect of reduced direct irradiance owing to increased cloud cover rather than anomalous downwelling longwave radiation.…”
Section: Impact On Compound and Concurrent Meteorological Extremes Ov...mentioning
confidence: 99%